2013
DOI: 10.1002/oby.20196
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of genetic and environmental risk factors with respect to body fat mass in children: Results from the ALSPAC study

Abstract: Objective: To evaluate if percentile-specific effects of genetic, environmental and lifestyle obesity risk factors on body mass index (BMI) might reflect gene-environment interactions with respect to the development of overweight. Design and Methods: Retrospective study with data of 2,346 children from the Avon Longitudinal Study of Parents and Children (ALSPAC), using quantile regression with body fat mass index (FMI) for children at the age of 9 years as outcome variable. We assessed interactions of an ''obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…A more recent analysis found an interaction between an eight SNP obesity gene score and mono and polyunsaturated fatty acid intake [160]. Among 2346 children with low unsaturated fat intake, the gene score was associated with increased body fat mass index yet no association was present among unexposed children [160].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 97%
See 1 more Smart Citation
“…A more recent analysis found an interaction between an eight SNP obesity gene score and mono and polyunsaturated fatty acid intake [160]. Among 2346 children with low unsaturated fat intake, the gene score was associated with increased body fat mass index yet no association was present among unexposed children [160].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 97%
“…Among 2346 children with low unsaturated fat intake, the gene score was associated with increased body fat mass index yet no association was present among unexposed children [160].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 99%
“…Numerous observational studies specifically investigated the interactions of obesity or body fat distribution associated SNPs or genetic risk scores (GRS) with nutrients [55,56,57,58,59,60,61], foods [55,62,63], dietary patterns [63,64,65,66,67], physical activity and other lifestyle factors [61,67,68,69,70,71]. In a previous cohort study, which included 334 female twins (57.7 ± 6.7 years), it was found that, when carrying a low genetic risk of abdominal fat, women in the highest tertile of polyunsaturated fat intakes had about 50% less central abdominal fat than those in the lowest tertile of intakes [61].…”
Section: Gene–environment Interaction On Obesity and Body Fat Distmentioning
confidence: 99%
“…We observed neither major percentile-specific associations nor evidence for effect modification by increased genetic susceptibility. While we had found corresponding association patterns for several risk factors of childhood overweight, such as maternal overweight, low parental education, or exclusive formula feeding (33), we had already observed less evidence for such patterns or for effect modification by genetic factors with respect to nutritional variables in a previous study (34). Based on these findings, we consider it rather unlikely that the associations of energy and protein intake with childhood overweight are largely driven by genetically susceptible subgroups, although we cannot rule out that other genetic variants that we were not able to investigate here may play a role.…”
Section: Pediatric Obesitymentioning
confidence: 78%